GRAPHITE-MELT EQUILIBRIA DURING MANTLE MELTING: CONSTRAINTS ON CO2 IN MORB MAGMAS AND THE CARBON CONTENT OF THE MANTLE - Holloway J.R. (My University, 1998)
Melts produced under fluid-absent, graphite-saturated conditions have tightly constrained oxidation states and CO2 contents. A model is presented for the generation of mid-ocean ridge basalt (MORB) magma by fluid-absent partial melting of graphite-saturated upper mantle. The model results in melt ferric/ferrous ratios and oxygen fugacities which are consistent with observed values in glassy MORBs and oceanic perioditites. Increasing the degree of partial melting causes decreases in the ferric/ferrous ratio of the melt, the oxygen fugacity, and the concentration of CO2 in the melt. Sensitivity analysis indicates that the initial ferric-iron concentration in the source region has the greatest effect on the results. For the range of probable initial values, the oxygen fugacity of the graphite-saturated primary MORB magma at 1 GPa is 2.5 log10 units below the Ni-NiO buffer, and the CO2 content of the melt ranges from 900 to 1800 ppm (mass). The amount of source region carbon consumed during partial melting is between 40 and 80 ppm. The dissolved CO2 in MORBs represents a flux of 3.5 to 7 # 1010 kg/year which is significantly greater than estimates based on the measured CO2 content of glassy MORB samples.
Keywords: MANTLE; BASALT; CARBON; DEGASSING